Dispersal syndromes in challenging environments: A cross‐species experiment. (12th October 2022) - Cote, Julien; Dahirel, Maxime; Schtickzelle, Nicolas; Altermatt, Florian; Ansart, Armelle; Blanchet, Simon; Chaine, Alexis S.; De Laender, Frederik; De Raedt, Jonathan; Haegeman, Bart; Jacob, Staffan; Kaltz, Oliver; et al.
Abstract: Dispersal is a central biological process tightly integrated into life‐histories, morphology, physiology and behaviour. Such associations, or syndromes, are anticipated to impact the eco‐evolutionary dynamics of spatially structured populations, and cascade into ecosystem processes. As for dispersal on its own, these syndromes are likely neither fixed nor random, but conditional on the experienced environment. We experimentally studied how dispersal propensity varies with individuals' phenotype and local environmental harshness using 15 species ranging from protists to vertebrates. We reveal a general phenotypic dispersal syndrome across studied species, with dispersers being larger, more active and having a marked locomotion‐oriented morphology and a strengthening of the link between dispersal and some phenotypic traits with environmental harshness. Our proof‐of‐concept metacommunity model further reveals cascading effects of context‐dependent syndromes on the local and regional organisation of functional diversity. Our study opens new avenues to advance our understanding of the functioning of spatially structured populations, communities and ecosystems. Abstract : Dispersal is a central biological process tightly integrated into life histories, morphology, physiology and behaviour. Such associations, or syndromes, are anticipated to impact the eco‐evolutionary dynamics of spatially structured populations, and cascade into ecosystem processes. With a coordinated distributed experiment involving five laboratories across Europe and 15 focal study organisms covering the tree of life, we demonstrate that dispersal is generally positively related to three ubiquitous and functionally important traits and that the harshness of environment strengthens the link between dispersal and morphological traits.